2010
DOI: 10.1073/pnas.1000869107
|View full text |Cite
|
Sign up to set email alerts
|

Auxins reverse plant male sterility caused by high temperatures

Abstract: With global warming, plant high temperature injury is becoming an increasingly serious problem. In wheat, barley, and various other commercially important crops, the early phase of anther development is especially susceptible to high temperatures. Activation of auxin biosynthesis with increased temperatures has been reported in certain plant tissues. In contrast, we here found that under high temperature conditions, endogenous auxin levels specifically decreased in the developing anthers of barley and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
272
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(282 citation statements)
references
References 25 publications
7
272
2
1
Order By: Relevance
“…Reduction in anther elongation was observed upon heat stress as a result of decreased auxin levels in the developing anthers. Reduced anther elongation upon heat stress has also been found in other species, such as barley (Sakata et al, 2010). The observations of Kim et al (2001) and Warner and Erwin (2005) are in line with our observation that natural variation exists both in terms of duration of the sensitivity window and the degree of reduction in seed set within the sensitivity window.…”
Section: Identification Of a Developmental Sensitivity Windowsupporting
confidence: 79%
See 1 more Smart Citation
“…Reduction in anther elongation was observed upon heat stress as a result of decreased auxin levels in the developing anthers. Reduced anther elongation upon heat stress has also been found in other species, such as barley (Sakata et al, 2010). The observations of Kim et al (2001) and Warner and Erwin (2005) are in line with our observation that natural variation exists both in terms of duration of the sensitivity window and the degree of reduction in seed set within the sensitivity window.…”
Section: Identification Of a Developmental Sensitivity Windowsupporting
confidence: 79%
“…These studies showed that heat stress inhibits anther dehiscence, thereby reducing the release of pollen. Heat stress also leads to shortening of the anthers, due to a reduced amount of auxin (Sakata et al, 2010), which results in a mismatch between the ripening of the stigma and anthers, preventing self-fertilization in bisexual monoecious plants. Moreover, viability of pollen is reduced by disruption of male meiosis upon heat stress (Endo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A complete understanding of temperature stress on pollen development must await further understanding of carbohydrate turnover during this phase. Interestingly, in a recent study in barley and Arabidopsis, high temperature stress reduced endogenous synthesis of auxin in developing anthers, an effect that was suggested to be related to pollen sterility since exogenously applied auxin restored fertility (Sakata et al, 2010).…”
Section: Page 9 Of 24mentioning
confidence: 99%
“…No specific data on seed set but pollen sterility indirectly would reduce seed set in this species Some heat stress/duration combination hampered stamen development (microsporogenesis, filament elongation and pollen maturation) Endogenous auxin synthesis seems to be hampered in anther wall and microspores and could explain sterility as exogenous auxin restored sterility Sakata et al, 2010 Primula sp 6ºC, 15ºC, and 26ºC, 15h/day. Seven populations of five species subjected to 3 different temperatures during 4 days after pollination and then returned to 15ºC.…”
Section: Prasad Et Al 2002mentioning
confidence: 99%
See 1 more Smart Citation